UNIT 14A.4 Generation of Recombinant Vaccinia Viruses - Earl, Patricia L. (Curr Protoc Microbiol, 2015)
This unit describes how to infect cells with vaccinia virus and then transfect them with a plasmid-transfer vector or PCR fragment to generate a recombinant virus. Selection and screening methods used to isolate recombinant viruses and a method for the amplification of recombinant viruses are described. Finally, a method for live immunostaining that has been used primarily for detection of recombinant modified vaccinia virus Ankara (MVA) is presented. This unit first describes how to infect cells with vaccinia virus and then transfect them with a plasmid-transfer vector or PCR fragment to generate a recombinant virus (see Basic Protocol 1). Also presented are selection and screening methods used to isolate recombinant viruses (see Basic Protocol 2) and a method for the amplification of recombinant viruses (see Basic Protocol 3). Finally, a method for live immunostaining that has been used primarily for detection of recombinant modified vaccinia virus Ankara (MVA) is presented (see Basic Protocol 4). HeLa S3 cells are recommended for large-scale growth of vaccinia virus. BS-C-1 cells may be used for xanthine-guanine phosphoribosyltransferase (XGPRT) and plaque size selection, fluorescent protein screening, transfection and determination of virus titer (UNIT 14A.3). For thymidine kinase (TK) selection, HuTK(−) 143B cells are used. With MVA, all steps are carried out in CEF or BHK-21 cells (UNIT 14A.3). CAUTION: Proceed carefully and follow biosafety level 2 (BL-2) practices when working with standard vaccinia virus (see UNIT 14A.3 for safety precautions). [*Copy Editor: The original CPMB unit referenced CPMB Unit 16.15 for safety. The chapter editor asked that the authors include some of the safety information in the revised units – CPMB 16.16 and 16.17 – which are now CPMC Unit 14A.3 and 14A.4. As a result, the authors changed the safety citation here to “Unit 14A.3”, which doesn’t have nearly as much information as the original CPMB Unit 16.15. Perhaps the reason is that some of those early safety concerns are no longer relevant, but it would be good if you could double check with the authors and ask why they elected not to add more safety information. If guidelines have been relaxed in the pox virus field, that would be good to say explicitly.] NOTE: Carry out all procedures for preparation of virus in a biosafety cabinet.